Air Fuel Ratio Study For Mixture Of Biogas And Hydrogen On Mild Combustion - M. M., Noor; Wandel, Andrew P.; Yusaf, Talal (Universiti Malaysia Pahang, 2014)
Air Fuel Ratio (AFR) is an important parameter to indicate the combustion quality. Lower AFR will result in Unburned Hydrocarbons (UHC) that harms the environment. This paper discusses the simulation of AFR for the Moderate or Intense Low oxygen Dilution (MILD) combustion using bluff-body burner. A low calorie biogas fuel of 50% methane, 20% hydrogen and 30% carbon dioxide were used in this simulation. The AFR will be evaluated based on the UHC produced and measured in the exhaust gas composition. Stoichiometric AFR produced zero UHC and zero excess Oxygen measured in the exhaust gas. UHC in the exhaust gas is a waste of fuel and is possible to create unwanted combustion at unwanted location. The study found that at AFR 4:1, almost zero UHC was detected in the exhaust gas pipe and Exhaust Gas Recirculation (EGR) pipe.